DEATH, MEMORY AND CENOTAPHS ON THE PANAMERICANA NORTE HIGHWAY BETWEEN LIMA AND TRUJILLO. - DE LA CRUZ VILLANUEVA, Carlos A. (2023)
The following article provides an approach to the understanding of the cenotaphserected on the margins of the great Panamericana Norte highway, whose analysiswas developed in the project “Cenotaphs on the coastal roads of Peru. Observationand historical analysis of the mortuary reminders on the margins of the NorthPan-American highway (Lima - Trujillo) 2021”, approved by the Ricardo PalmaUniversity, on August 24, 2021 in the agreement of the University Council No. 1668- 2021- virtual . This work is a brief synthesis, which proposes to understand, fromthe spectrum of history, one of the expressions before death or tributes to theloss, developed in our regional daily life that runs along the North Pan-Americanhighway between the cities of Lima and Trujillo.